Computing Today - Timothy J. O'Leary (Mc Graw Hill, 2004)
This book delivers the most up-to-date information about the IT world with features like: careers in IT (job descriptions for different IT careers, including job titles, responsibilities, educational requirements, and salary ranges, making IT work for you (coverage of special interest topics like down-loading music from the internet and creating personal Web sites), using IT at DVD direct (a running case that follows Alice, a recent college graduate hired as a marketing analyst, as she gathers and process data to help manage dan accelerate the growth of the company), on the web explorations (marginal elements that direct you to connect with carefully chosen web sites that give you current information about selected topics), and a look to the future (discussion of recent technological advances relating to chapter material). We can learn more than just how to surf and rip: use "Computing Today" to find out about the latest trends in Information Technology (IT) and how you can apply this knowledge in the workplace.